MOTIVASI PADA REHABILITASI PASKA STROKE - Elisa Anderson (Jurnal Skolastik Keperawatan, 2019)
High motivation is needed by post-stroke patients who follow rehabilitation to get maximum results. The purpose of this study was to analyze the relationship between motivation and achievement of rehabilitation of post-stroke patients. The method of this study was an analytic observational study with a cohort study design. The sample in this study was selected using consecutive sampling technique with a total of 14 respondents in proprioceptive neuromuscular facilitation (PNF) rehabilitation and 12 respondents in mirror therapy (MT) rehabilitation. The findings of this study were that all respondents had high motivation with a mean of 26.36 for PNF and 28.83 for MT, mean achievement of PNF rehabilitation (pretest-posttest: 47.14-49.64; mean different: 2.5) through instruments Barthel index and mean MT rehabilitation outcomes (pretest-posttest: 2.5-2.58; mean different: 0.08) through the muscle strength scale. Based on the pearson correlation analysis states that there is no significant relationship between motivation and PNF rehabilitation achievement (p=0.1; p>0.05) and there is no significant relationship between motivation and achievement of MI rehabilitation (p=0.351; p>0.05). Although all respondents were highly motivated and there was an increase in rehabilitation outcomes, the condition could not make the relationship statistically significant. The addition of larger and more varied respondents, and a longer period of time needs to be done for the development of this research.